Hydrothermal ageing of hydrophobic nano-calcium carbonate/epoxy nanocomposites. (September 2021) - Sugiman, Sugiman; Salman, Salman; Anshari, Buan
Highlights: The combined effect of hydrophobic nano calcium carbonate content and temperature on water absorption of epoxy nanocomposites was investigated. Anomalous water absorption in the hydrophobic nano calcium carbonate/epoxy nanocomposites was observed. Hydrophobic nano calcium carbonate increased water absorption of epoxy nanocomposites. The tensile properties of hydrophobic nano calcium carbonate/epoxy nanocomposites were improved both in unaged and aged condition. Abstract: In this study, we investigated the effects of the filler content and ageing temperature on the water absorption and tensile properties of hydrophobic nano-calcium carbonate (NCC)/epoxy nanocomposites. The NCC content of the nanocomposites was varied from 0 to 5 wt%, while the ageing temperature was set at 28, 45, and 55°C in a distilled water bath. The nanocomposites exhibited the non-Fickian behaviour at all the NCC contents and ageing temperatures. In general, the water absorption of the nanocomposites increased after the addition of NCC. Meanwhile, the diffusivity of the nanocomposites decreased with an increase in the NCC content; however, this decrease became less significant at higher ageing temperatures. Although the addition of 1–3 wt% NCC significantly increased the water uptake capability of the nanocomposites, it resulted in an improvement in their tensile properties at high temperatures and prolonged ageing times.